Branding of Russian payment system - Case Study Payment system “MIR” - Trofimchuk, Iuliia (2017)
The thesis explores the theme of branding in the banking system in Russia and the process of creating and promoting a new product such as the national payment system and its importance in the business practices of companies. The theoretical part of the research describes the key theoretical aspects related to branding, Its characteristics in Russia and the banking system and the process of its formation. The practical part explores the process of introducing and promotion of a payment system on the example of one Russian bank. In addition, the advantages of the product will be considered in front of international payment systems - Visa and MasterCard and among competitors in the Russian market. The purpose of the thesis was to analyze each branding process in the banking system of such a large product as the national payment system and to find out what results of bank and that system in general had by the end of 2016, what opinion of the population of Russia about the national payment system "MIR".